Towards inclusive and sustainable strategies in smart cities: A comparative analysis of Zurich, Oslo, and Copenhagen - Oluwadamilola A. Oyadeyi; Olajide O. Oyadeyi (Research in Globalization)
Urbanisation has increased the need for sustainable urban development by positioning smart cities as critical frameworks for addressing environmental, economic, and social challenges. This study evaluates the sustainability strategies of three leading smart cities Zurich, Oslo, and Copenhagen by examining their environmental footprint, energy consumption, waste management, and air quality. The study uses a PRISMA-based systematic literature review to put together evidence from peer-reviewed articles published between 2017 and 2024. The Critical Appraisal Skills Program (CASP) was used to assess the quality of the articles. The study reveals that smart mobility and waste-to-energy systems drive Zurich’s strengths in urban densification and public transportation, Oslo’s leadership in renewable energy and electric mobility, and Copenhagen’s ambitious carbon–neutral initiatives. Despite these achievements, challenges such as high implementation costs, slow technological adoption, and social equity issues persist, emphasising the complexity of achieving inclusive and sustainable urban evolution. To address these challenges, this study recommends increasing public participation through inclusive urban planning and digital platforms, strengthening policy frameworks, and funding for sustainability projects, and investing in data collection technologies to monitor real-time environmental impacts. Furthermore, fostering cross-city collaboration and addressing energy consumption challenges associated with AI and IoT are essential for scaling successful models globally. These insights offer actionable guidance for policymakers and urban planners to improve sustainability strategies and ensure long-term benefits.